1995
DOI: 10.1002/psc.310010108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and lodination of human (phenylalanine13, tyrosine19) melanin‐concentrating hormone for radioreceptor assay

Abstract: An analogue of human melanin-concentrating hormone (MCH) suitable for radioiodination was designed in which Tyr13 and Val19 of the natural peptide were replaced by phenylalanyl and tyrosyl residues: [Phe13, Tyr19]-MCH. The peptide was synthesized by the continuous-flow solid-phase methodology using Fmoc-strategy and polyhipe PA 500 and PEG-PS resins. The linear MCH peptides with either acetamidomethyl-protected or free cysteinyl residues were purified to homogeneity and cyclized by iodine oxidation, yielding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
(1 reference statement)
0
23
0
1
Order By: Relevance
“…Tables I-III were prepared by solid-phase syntheses as described under "Experimental Procedures." They were evaluated for their respective binding affinities for cloned human MCH receptor 1 and 2 in the competition binding assays with 125 I-[Phe 13 ,Tyr 19 ]hMCH as the radiolabeled ligand (28) and, also, for their ability to stimulate inositol trisphosphate-coupled mobilization of intracellular calcium in human HEK-293 cells expressing hMCH-1R and hMCH-2R (24,29,30).…”
Section: Methodsmentioning
confidence: 99%
“…Tables I-III were prepared by solid-phase syntheses as described under "Experimental Procedures." They were evaluated for their respective binding affinities for cloned human MCH receptor 1 and 2 in the competition binding assays with 125 I-[Phe 13 ,Tyr 19 ]hMCH as the radiolabeled ligand (28) and, also, for their ability to stimulate inositol trisphosphate-coupled mobilization of intracellular calcium in human HEK-293 cells expressing hMCH-1R and hMCH-2R (24,29,30).…”
Section: Methodsmentioning
confidence: 99%
“…First strand cDNA (corresponding to 1 g of total RNA) was subjected to 35 cycles of amplification using the forward primer 5Ј-GAGACCCAAGCTTCTGGATGGACCTGGAAGCCT-3Ј and the reverse primer 5Ј-GATGACGCGGCCGCTCAGGTGCCTTTGCTTTCTG-3Ј (33). After an initial cycle of denaturation at 94°C for 1 min, polymerase chain reaction was carried out for 35 cycles with the following cycle conditions: 94°C, 1 min; 55°C, 1 min; 72°C, 3 min with a postincubation of 72°C for 7 min.…”
Section: Cloning Of the Human Mch Receptor (Slc-1)-human Brain Poly(a)mentioning
confidence: 99%
“…It was also shown that the MCH ring was essential (32) and that any modification (including amino acid deletion) of this ring was deleterious for biological activity (30). A second series of data have been published more recently using membranes from mammalian cells that were tested for their capacity to bind the current labeled derivative of MCH, [Phe 13 ,Tyr 19 ]MCH (15,16,(33)(34)(35)(36). Among other discrepancies, the reported affinities for salmon MCH in the cell lines used (16,34) were quite different from those reported at the rat or human cloned receptor (17,21).…”
mentioning
confidence: 99%
“…3C). [Phe 13 , Tyr 19 ]-MCH, a synthetic analog of MCH known to bind to and activate MCHR1 (8,12,22), also activates MCHR2, with a slightly lower potency compared with MCH. Other peptides from the same MCH precursor neuropeptide-EI and neuropeptide GE (23,24) were inactive for MCHR2.…”
Section: Resultsmentioning
confidence: 99%